2015
DOI: 10.1186/s13041-015-0140-z
|View full text |Cite
|
Sign up to set email alerts
|

Persistent pain alters AMPA receptor subunit levels in the nucleus accumbens

Abstract: BackgroundA variety of pain conditions have been found to be associated with depressed mood in clinical studies. Depression-like behaviors have also been described in animal models of persistent or chronic pain. In rodent chronic neuropathic pain models, elevated levels of GluA1 subunits of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors in the nucleus accumbens (NAc) have been found to inhibit depressive symptoms. However, the effect of reversible post-surgical pain or inflammatory pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 92 publications
2
28
0
Order By: Relevance
“…In these studies on rewards, the length of time required to increase GluA1 levels is in general compatible with the time course found in our study. Similarly, in a previous study on AMPA receptor trafficking, GluA1 upregulation at the NAc synapse is found to occur after pain has become persistent or chronic [52]. Thus, we speculate that GluA1 upregulation in the core and shell of NAc in persistent pain states may represent a form of homeostatic plasticity in the reward system.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In these studies on rewards, the length of time required to increase GluA1 levels is in general compatible with the time course found in our study. Similarly, in a previous study on AMPA receptor trafficking, GluA1 upregulation at the NAc synapse is found to occur after pain has become persistent or chronic [52]. Thus, we speculate that GluA1 upregulation in the core and shell of NAc in persistent pain states may represent a form of homeostatic plasticity in the reward system.…”
Section: Discussionsupporting
confidence: 79%
“…A previous study has shown that increases in GluA1 levels at the NAc synapse do not manifest until at least 7 days after SNI, suggesting that persistent pain, rather than acute nerve injury, triggers the synaptic targeting of GluA1 subunits [52]. More importantly, increased GluA1 delivery to the NAc synapse has also been demonstrated in a persistent inflammatory pain model that does not involve nerve injuries [52]. Thus, we believe that chronic pain, rather than nerve injury, causes the GluA1 increases observed in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). 35,39 This sensory hypersensitivity lasted up to 4 days after incision, and it resolved by the 7 th day post-incision 18,39 (Fig. 1A).…”
Section: Resultsmentioning
confidence: 96%
“…18,35,39 Briefly, rats were anaesthetized with Isoflurane anesthesia (1.5 to 2%), and the plantar surface of the right hind paw was sterilized and prepared. A 1.5 cm longitudinal incision was made with a number 10 scalpel, through skin and fascia of the right plantar aspect of the paw.…”
Section: Methodsmentioning
confidence: 99%